Benefits of exclusive breastfeeding: An integrative review - Germano Rodrigues Couto; Vanessa Dias; Isabel de Jesus Oliveira (Tehran University of Medical Sciences, 2020)
Background & Aim: The importance of breastfeeding and its exclusivity in the first six months of the child's life, is worldwide recognized. Despite that, adherence to exclusive breastfeeding is far from international standards. Therefore, updating evidence on this topic is essencial to demonstrate to parents and health professionals, the benefits of exclusive breastfeeding, demystifying ideas and promote adherence. Materials & Methods: An  integrative  review  was  conducted  with  a  search  in Medline,  SciELO  and  CINHAL  databases,  with  the  descriptors  "breast feeding", "breast", "feeding", "breastfeeding", "exclusive" and "benefits",  combined  with  the  Boolean  operator  "AND" and "OR",  from  studies  published  between  2014  and  2019. Of the 221 studies identified, eight were included for review. Results: Short-term and long-term benefits of exclusive breastfeeding for children were identified, such as healthier eating habits, reduced length of hospital stay, favorable weight increase, lower body mass index, lower adiposity, lower total cholesterol values, better cognitive and behavioral development, as well as stability of metabolic levels in children with metabolic disorders. Conclusion: There are benefits for exclusive breastfeeding that must be explained to parents. Nurses must incorporate the best available evidence into their practice to enable parents to realise the impact of the choice of exclusive breastfeeding on the child's health, increasing their adherence.